Water-based lubricants formulated with hybrid MXene and ionic liquid additives: effects of carboxylmethyl cellulose and xanthan gum surfactants on dispersion stability, viscosity, interface temperature and tribological performance - Ibrahim, M. S.; Sulaiman, M. H.; Ismail, M. I.S.; Yaakob, Y.; Ridzuan, M. J.M. (Elsevier B.V., 2025)
During pure asperity contact, insufficient film thickness in Water-based Lubricants (WBLs) significantly contributes to poor friction and high interface temperature, altering their structure, viscosity and boundary lubrication properties. This study investigates the effects of surfactants, Carboxymethyl Cellulose (CMC) and Xanthan Gum (XG), combined with two-dimensional MXene and Ionic Liquid (IL) additives in WBLs to optimize formulation, dispersion stability, viscosity and tribological performance. The XG surfactant demonstrated improvements in viscosity and dispersion stability compared to CMC. However, the combination of hybrid MXene and IL additives with CMC surfactant (CMC_MXene/IL) led to lowest friction and wear compared to individual MXene or IL additives. Overall, surfactants enhanced lubrication mechanism, facilitating a transition from boundary to hydrodynamic lubrication.